Adherence factors to physical activity programs for older adults: the experience of the participants of the "Without Borders" project - Souza, Doralice Lange de; Vendrusculo, Rosecler (Brazilian journal of physical education and sport, 2010)
This paper discusses the results of a qualitative research project that had as a goal to investigate adherence factors to a physical activity program for older adults in Brazil named "Sem Fronteiras: Atividades Corporais Para Adultos Maduros e Idosos", which translated into English means "Without Borders: Physical Activities for Mature and Older Adults". The participants of the study were 10 older adults who had been in the project for at least two years. Data were collected through semi-structured in-depth interviews with open-ended questions. The leading interview questions were: What led you to start the program? What motivates you to continue attending the program? What are the main difficulties you find in continuing to attend the program? What motivates you to overcome these difficulties? The coding categories emerged from the data. Initially, we analyzed the data for each of the research participants, raising and coding the main themes that emerged from their responses. Next, we did a cross-analysis of the data of all participants looking for similarities and differences between the themes. Our main finding was that the participants adhere to the project not only because of the benefits that they perceive in terms of their physical, mental and emotional health, but also because it offers them opportunities for their personal development, socialization, and exchange of experiences, information, support, and affection. The main barriers that the interviewees found to keep participating in the project were health problems and family commitments.